(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical and subclinical characteristics premature rupture of membranes at pregnancies at gestational age from 24 to 34 weeks at Hanoi Obstetrics and Gynecology Hospital. Materials and method: A retrospective cross-sectional descriptive study on 217 pregnant women with preterm rupture of membranes at gestational age from 24 weeks 0 day to 33 weeks 6 days at Hanoi Obstetrics and Gynecology Hospital from January 2022 to December 2022. Results: The average age of pregnant women was 30.1±6.1. Premature rupture of membranes is common in pregnant women with a history of previous cesarean section (33.2%), history of abortion (20.7%), and miscarriage and stillbirth (15.6%). Most women with premature rupture of membranes have normal amniotic index (64.5%) when admitted to the hospital. The number of white blood cells in the mother’s blood <15,000/mm3 accounts for the majority (82.5%). The rate of amniotic infection in the group with time from rupture of membranes to hospital admission ≥ 6 hours (30.6%) is higher than in the group <6 hours (6.8%). Among pregnant women who had vaginal fluid cultures, 8.5% white Staphylococcus and 7.4% E. coli were found. Conclusion: The majority of pregnant women with premature rupture of membranes admitted to the hospital have normal amniotic index, clear amniotic fluid, no increased BC in the blood, amniotic infections increase when hospitalization time is >6 hours. Staphylococcus aureus and Ecoli are most commonly found in vaginal fluid cultures.